2006
DOI: 10.1080/09546630500497249
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term oral isotretinoin therapy does not cause clinical or subclinical peripheral neuropathy

Abstract: Short-term administration of oral isotretinoin in young patients does not cause clinical or subclinical neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Studies in humans have employed doses of curcumin as low as 10 or 20 μM 35 , the concentrations we used in our experiments, and doses as high as to 8,000 mg/day without causing adverse events 36-38 . In our study, both doses reduced NTD incidence when used under high glucose conditions, suggesting that a low concentration of curcumin may be effective.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in humans have employed doses of curcumin as low as 10 or 20 μM 35 , the concentrations we used in our experiments, and doses as high as to 8,000 mg/day without causing adverse events 36-38 . In our study, both doses reduced NTD incidence when used under high glucose conditions, suggesting that a low concentration of curcumin may be effective.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, sensorial neuropathy was detected in 18 patients treated with systemic isotretinoin (1 mg/kg/day) at the rates of 44% and 83% in electrophysiological evaluations at three and six months, respectively. 6 However, Chroni et al 11 failed to detect clinical or electrophysiological neuropathy in 18 patients treated with systemic isotretinoin (1 mg/kg/day) at one and three months. These differences can be related to duration or dose of isotretinoin use.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 There is conflicting data in the literature regarding peripheral neuropathy related to isotretinoin use. 6,11,12 In a study by Canpolat et al, 12 no neuropathy was detected by electrophysiological evaluations in 15 patients Figure 1. Magnetic resonance imaging findings during drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects involving the CNS include depression, headache, disulfiram-like reactions, pseudotumor cerebri, oculogyric crisis, and decreased hearing.5,6 In addition, in the literature, some studies showed that second-generation retinoid (acitretin) treatment can affect the PNS. It can cause sensory nerve fiber dysfunction,7 peripheral sensory neuro pathy, and sensorimotor polyneuropathy.8,9 Also, a nerve biopsy study showed decreases in small and large myeli nated fibers, macrophages, extensive axonal degeneration, and abnormal Schwann cell complexes.10 However, reports of the effects of isotretinoin treatment on the PNS are conflicting.11, 12 Fraunfelder and colleagues reported ocular inflamma tion and optic neuritis in patients using oral isotretinoin treatment but could not find a relationship between the therapy and ocular pathology. 13 Aydogan and colleagues studied the effects of oral isotretinoin treatment on the ocular nerve fibers and retinal function but could not find significant data regarding the synaptic activity and propagation of action potentials.14 In addition, they found an increased latency of P100 waves after therapy in 18% of patients by using visual evoked potentials.…”
Section: Discussionmentioning
confidence: 97%